Asymmetries of reproductive isolation are reflected in directionalities of hybridization: integrative evidence on the complexity of species boundaries. Issue 3 (7th September 2020) - Keller, Barbara; Ganz, Rita; Mora‐Carrera, Emiliano; Nowak, Michael D.; Theodoridis, Spyros; Koutroumpa, Konstantina; Conti, Elena
Summary: The complex nature of species boundaries has been a central topic in evolutionary biology ever since Darwin. Despite numerous separate studies on reproductive isolation and hybridization, their relationship remains underinvestigated. Are the strengths and asymmetries of reproductive barriers reflected in the extent and directionalities of interspecific genetic exchange? We combined field, experimental, and molecular data to quantify strengths and asymmetries of sympatric reproductive barriers and hybridization between florally heteromorphic primroses. We also assessed whether generalist pollinators discriminate between different floral cues and contribute to reproductive isolation, a long‐debated topic. Sympatric reproductive isolation is high but incomplete, and most phenotypic intermediates are genetic F1 hybrids, whereas backcrosses are rare, revealing low interspecific gene flow. Species integrity rests on multiple barriers, but ethological isolation is among the strongest, demonstrating that even generalist pollinators crucially contribute to the maintenance of species boundaries. Furthermore, reproductive barriers are weaker for Primula veris and short‐styled plants, results corroborated by molecular data. Thus, in florally heteromorphic systems, both species‐ and morph‐dependent asymmetries affect permeability of species boundaries. Our study illustrates how the interactions between complex floral syndromes and pollinators shape species boundaries in unique, previously undescribed ways.